2011
DOI: 10.1080/19415257.2010.517399
|View full text |Cite
|
Sign up to set email alerts
|

Early career teachers’ emotional experiences and development – a Norwegian case study

Abstract: Emotional experiences that are an integral part of the process of becoming teachers have been insufficiently explored in the research literature. The early experiences of three new teachers in a Norwegian upper secondary school are analysed using a collective case-study design and a socio-cultural theoretical framework. Emotions arising in the classroom and in collaboration with colleagues are focused on, as well as how emotions are communicated. Data illuminate differing ways of adjusting to the emotional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…In addition to this, we need to consider the resilience of the learner, that is, how they handle and learn from failure; Duckworth, Peterson, Matthews, and Kelly's (2007) work on grit (consistency of effort and perseverance of effort) is useful to consider in this respect. Furthermore, the extent to which the nature of feedback matches an individual's personal vision, how the individual manages this, and the nature of networks drawn upon are also important (Jakhelln, 2011).…”
Section: Power: the Respective Roles Of Student And Lecturer Within Tmentioning
confidence: 99%
“…In addition to this, we need to consider the resilience of the learner, that is, how they handle and learn from failure; Duckworth, Peterson, Matthews, and Kelly's (2007) work on grit (consistency of effort and perseverance of effort) is useful to consider in this respect. Furthermore, the extent to which the nature of feedback matches an individual's personal vision, how the individual manages this, and the nature of networks drawn upon are also important (Jakhelln, 2011).…”
Section: Power: the Respective Roles Of Student And Lecturer Within Tmentioning
confidence: 99%
“…Katz et al's (2012) recent review of emotion coaching research calls for more studies that explore the role of emotion socialisation agents other than parents, such as teachers and peers. Productive interactions between individuals are fundamental to effective educational practice, and teachers have identified that emotional management is integral to their work (Gross, 2013;Day et al, 2006;Nias 1996;Sutton et al, 2009), yet the exact training needs and skill base on which to support the development of reflective, emotional competencies are yet to be identified (Ahn and Stifter 2006;Jakhelln, 2010;OFSTED, 2013).…”
Section: Problem Statementmentioning
confidence: 99%
“…Each of the latter three studies refers to Goleman's (1995) work and thus relies more or less explicitly on the idea of EI as comprising four main components: self-awareness, self-management, social awareness (empathy), and relationship management (collaboration). Emotional labour: Three studies elaborate emotions via the notion of emotional labour (Seymour and Sandiford 2005;Jakhelln 2010;Webb 2012). All three stress the importance of emotional rules in their understanding of emotions.…”
Section: The Understanding Of Emotionsmentioning
confidence: 99%
“…Emotions Influencing Identity Learning All four papers in this sub-category elaborate how emotions that influence identity learning carry forward into teachers' work or career development (Meijers 2002;Geijsel and Meijers 2005;McNally et al 2009;Jakhelln 2010). The papers share the finding that emotions are important in identity learning at the start of one's career and, further, that they constitute an important aspect of workplace learning in the course of one's career.…”
Section: Learning At Work As a Phenomenon Influenced By Emotionsmentioning
confidence: 99%